2015
DOI: 10.1126/science.1261768
|View full text |Cite
|
Sign up to set email alerts
|

The weakening summer circulation in the Northern Hemisphere mid-latitudes

Abstract: Rapid warming in the Arctic could influence mid-latitude circulation by reducing the poleward temperature gradient. The largest changes are generally expected in autumn or winter, but whether significant changes have occurred is debated. Here we report significant weakening of summer circulation detected in three key dynamical quantities: (i) the zonal-mean zonal wind, (ii) the eddy kinetic energy (EKE), and (iii) the amplitude of fast-moving Rossby waves. Weakening of the zonal wind is explained by a reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
338
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(368 citation statements)
references
References 40 publications
26
338
4
Order By: Relevance
“…While many of the above-described atmospheric modes of variation also have been linked to increasing wildfire activity in the western United States [21,54,[57][58][59][60], caution must be taken when establishing direct causal linkages between declining ASIE and increasing wildfire activity through correlative analyses. In short, low (high) levels of ASIE perturb atmospheric flow through interactions with latitudinal temperature gradients, which in turn can impact atmospheric thickness, zonal (meridional) flow patterns [12,16] and surface climatic conditions associated with both wildfire and specific modes of variation [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many of the above-described atmospheric modes of variation also have been linked to increasing wildfire activity in the western United States [21,54,[57][58][59][60], caution must be taken when establishing direct causal linkages between declining ASIE and increasing wildfire activity through correlative analyses. In short, low (high) levels of ASIE perturb atmospheric flow through interactions with latitudinal temperature gradients, which in turn can impact atmospheric thickness, zonal (meridional) flow patterns [12,16] and surface climatic conditions associated with both wildfire and specific modes of variation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the processes is constantly evolving (e.g., [13,14]) with recent research suggesting that, among others, ASIE is potentially a controlling factor or interacts with (1) the Atlantic multidecadal oscillation (AMO; [14]); (2) the NAO [13,15]; (3) the western Pacific pattern (WP) and El Nino Southern Oscillation (ENSO; [15]); (4) declining summertime total kinetic energy and zonal flow [16]; (5) the Pacific Decadal Oscillation (PDO; [17]); (6) surface temperature extremes [10]; and (7) surface precipitation extremes [18,19]. An example of the evolution of our understanding of the linkages includes studies [13,20], which found that contrary to earlier work based on empirical data [2,5], model simulations show that lower levels of ASIE are associated with reductions in wintertime cold events in Northern Europe, not increases in these events.…”
Section: Introductionmentioning
confidence: 99%
“…This might have favored a northward shift of the North Atlantic summer storm track (e.g., Ogawa et al 2012;Dong et al 2013a and2013b;Duchez et al 2016), which would result in reduced precipitation in summer 2015 over central Europe (Supplemental Fig. S12.1g) | Arctic might also be a factor for the 2015 summer heat wave (Coumou et al 2015).…”
Section: S57mentioning
confidence: 99%
“…State-of-the-art global climate models reveal that changes in zonal wind depend on the temperature structure of the lower atmosphere (Haarsma et al, 2013) and that zonal-mean zonal wind and eddy kinetic energy decline almost linearly in time due to polar amplification (Coumou et al, 2015). There are also natural sources of variability at up to decadal timescales.…”
Section: Introductionmentioning
confidence: 99%